Educational intervention to reduce overweigth and obesity in primary school children in Lima - Tarqui-Mamani, Carolina Beatriz (2023)
Objective: To evaluate the impact of an educational intervention in reducing the prevalence of overweight and obesity, in diet and in the levels of physical activity of primary school children. Methods: The study was quantitative, analytical, quasiexperimental. The sample consisted of 272 elementary school students, divided into two groups of 136 children each, with intervention and without educational intervention. Nutritional status was measured at the beginning and after the educational intervention in both groups. The intervention consisted of carrying out training activities on healthy eating, healthy lifestyle, wáter intake and physical activity, all through playful games and educational workshops. The study was approved by the Research Ethics Committee of the Universidad Nacional Mayor de San Marcos (UNMSM - School of Medicine). Reults: The age of the students was between 6 and 14 years old, after the educational intervention the prevalence of overweight decreased by approximately 5 percentage points (pp) and obesity by almost 1 pp in the intervened group, but the variations were not significant. In the group without intervention, the prevalence of overweight decreased by approximately 5 pp and obesity increased by almost 4 pp. Discussion: The reduction of excess weight did not occur in the expected percentages. and the educational intervention allowed to reduce the prevalence of overweight in the intervened group compared to the non-intervened group. A greater commitment of authorities is needed to promote regulatory strategies of the school environment to face the problem of obesity.